PEMBATASAN KEPEMILIKAN MOBIL BAGI SETIAP WARGA YANG TIDAK MEMILIKI GARASI DI PERUMAHAN PENJARINGAN SARI - Putri, Risya Tatamara Avinka Putri; Kurniawan, Muhammad Faris; Alfian, Muhammad Dicky (Mimbar Keadilan, 2020)
AbstractThe unavailability of a car garage in a house owned by a residential community causes many residents to park their cars on the shoulder of the residential road or in front of their homes, causing discomfort and is considered to interfere with the activities of the housing community. Especially if residents still park their cars in front of houses or on the shoulder of residential roads continuously and do not even obey the rules that have been made for a long time. The purpose of this study is to find out why housing residents still park their cars in front of the house or on the shoulder of the road and ignore the rules that have been made and what legal measures and sanctions will be given to residents who still park their cars in front of the house or on the shoulder of the residential road. The research method used in this research is to use a normative research method by conducting an explanation of the problem. Based on the results of this study, it is known why the citizens parked their cars in front of the house or shoulder of the road as well as legal efforts and sanctions provided for violators of these rules.Keywords: legal effects; parking; residentsAbstrakKetidaktersediaannya garasi mobil di rumah milik warga perumahan menimbulkan banyaknya warga yang memarkirkan mobilnya di bahu jalan perumahan atau di depan rumah mereka mengakibatkan ketidaknyamanan dan dianggap menggangu aktifitas masyarakat perumahan tersebut. Apalagi jika warga masih saja memarkirkan mobilnya di depan rumah atau di bahu jalan perumahan secara terus menerus dan bahkan tidak mematuhi aturan yang telah dibuat dalam jangka waktu yang lama. Tujuan penelitian ini adalah untuk mengetahui mengapa warga perumahan masih memarkirkan mobilnya di depan rumah atau di bahu jalan dan mengabaikan aturan yang telah dibuat serta upaya hukum dan sanksi apakah yang akan diberikan kepada warga yang masih saja memarkirkan mobilnya di depan rumah atau di bahu jalan perumahan. Metode penelitian yang digunakan dalam penelitian ini adalah menggunakan metode penelitan  normatif dengan melakukan pemaparan atas permasalahan tersebut. Berdasarkan hasil penelitian ini maka diketahui alasan warga memarkirkan mobilnya di depan rumah atau bahu jalan serta upaya hukum dan sanksi yang diberikan bagi pelanggar aturan tersebut.Kata kunci: akibat hukum; parkir; warga